2014
DOI: 10.3390/ani4020241
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Bedding Requirements during Transport and Monitoring Skin Temperature during Cold and Mild Seasons after Transport for Finishing Pigs

Abstract: Simple SummaryTypically, bedding is used to improve pig comfort and welfare during transport. This study assesses the level of bedding required during transport of finishing pigs in semi-truck trailers. The present study shows that adding more than six bales/trailer of bedding in cold weather and more than three bales/trailer of bedding in mild weather provides no benefit to the pigs. Economic forces would not favor increased bedding with no benefit. Use of infrared thermography may provide a useful tool to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 15 publications
(18 reference statements)
2
19
0
Order By: Relevance
“…The three bedding depths used in these trips did not provide any observable additional thermal insulation to the pigs, as measured by differences in pig surface temperature. This result agrees with a recent study [34], which reported no significant effect on the thermal environment for 3–12 bags of bedding for outdoor temperatures ranging from −13 to 45 °C (8 to 113 °F). In that study, the trailer was divided into four compartments, and five laser thermometers were used to collect pig surface temperature on the flank/side of ten randomly selected pigs during unloading.…”
Section: Resultssupporting
confidence: 93%
“…The three bedding depths used in these trips did not provide any observable additional thermal insulation to the pigs, as measured by differences in pig surface temperature. This result agrees with a recent study [34], which reported no significant effect on the thermal environment for 3–12 bags of bedding for outdoor temperatures ranging from −13 to 45 °C (8 to 113 °F). In that study, the trailer was divided into four compartments, and five laser thermometers were used to collect pig surface temperature on the flank/side of ten randomly selected pigs during unloading.…”
Section: Resultssupporting
confidence: 93%
“…Skin temperature recorded immediately before unloading (TbU) considers that the vehicle is stationary and there is no air flow, as a result the temperature of the front compartments rises, which carries a microclimate inside the livestock container with thermal variations, and thereby influences the welfare of pigs (WESCHENFELDER et al, 2013). In this sense, Mcglone et al, (2014) found temperature of the swine skin surface from the vehicles increased linearly with the increasing outside air temperature. In addition, the air temperature inside and outside of the truck during the journey can influence the loss of quantities of heat and fluids due to panting and sweating, and it is possibly related with enthalpy, which is the heat energy of the air surrounding the animal, dictating the degree of heat loss inside the trailer (VILLARROEL et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Bedding was provided by the trucking company. Bedding levels were based on findings from McGlone et al [ 9 ], and were randomly assigned to the trailers. Assigned levels were 0.6 m 3 bedding, 1.2 m 3 bedding, and 2.4 m 3 bedding.…”
Section: Methodsmentioning
confidence: 99%
“…A typical transport experience had a loading phase in which trailer temperature warms up. When the truck and trailer move, the trailer cools and reaches an equilibrium temperature (after 30 minutes) that depends primarily on outside temperature since trailers had a uniform number of pigs [ 9 ]. The trailer temperature then changes again when the truck and trailer stops and waits to unload and then it changes again during unloading.…”
Section: Methodsmentioning
confidence: 99%